Understanding and Predicting the Gulf of Mexico Loop Current: Critical Gaps and Recommendations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
One of the most significant, energetic, yet not well understood, oceanographic features in the Americas is the Gulf of Mexico Loop Current System (LCS), consisting of the Loop Current (LC) and the Loop Current Eddies (LCEs) it sheds. Understanding the dynamics of the LCS is fundamental to understanding the Gulf of Mexico's full oceanographic system, and vice versa. Hurricane intensity, offshore safety, harmful algal blooms, oil spill response, the entire Gulf food chain, shallow water nutrient supply, the fishing industry, tourism, and the Gulf Coast economy are all affected by the position, strength, and structure of the LC and associated eddies.
Keywords: Earth Sciences

Advancing Understanding of Offshore Oil and Gas Systemic Risk in the U.S. Gulf of Mexico: Current State and Safety Reforms Since the Macondo Well–Deepwater Horizon Blowout - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Most of the offshore oil and gas industry in the Gulf of Mexico has shown considerable improvement in systemic risk management, which is now approaching a middle stage of maturity across most risk elements. Advancing Understanding of Offshore Oil and Gas Systemic Risk in the U.S. Gulf of Mexico: Current State and Safety Reforms Since the Macondo Well–Deepwater Horizon Blowout assesses both industry and regulatory progress against the reforms that were recommended following the Deepwater Horizon disaster in 2010. The report also states that progress has been uneven, and critical gaps remain in comprehensively addressing the management of systemic risk offshore.
Keywords: Environment and Environmental Studies

Gulf Research Program Annual Report 2021 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Each year, the Gulf Research Program (GRP) produces an annual report to summarize how funds were used. These reports review accomplishments, highlight activities, and, over time, will assess metrics to determine how the program is progressing in accomplishing its goals. The 2021 annual report is the eighth report in this series. The GRP is an independent, science-based program founded in 2013. Through grants, fellowships, and other activities, it seeks to enhance oil system safety and the protection of human health and the environment in the Gulf of Mexico region and other areas along the U.S. outer continental shelf with offshore oil and gas operations.
Keywords: Environment and Environmental Studies

Gulf Research Program Annual Report 2020 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Each year, the Gulf Research Program (GRP) produces an annual report to summarize how funds were used. These reports review accomplishments, highlight activities, and, over time, will assess metrics to determine how the program is progressing in accomplishing its goals. The 2020 annual report is the seventh report in this series. The GRP is an independent, science-based program founded in 2013. Through grants, fellowships, and other activities, it seeks to enhance oil system safety and the protection of human health and the environment in the Gulf of Mexico region and other areas along the U.S. outer continental shelf with offshore oil and gas operations.
Keywords: Environment and Environmental Studies

The Gulf Research Program Annual Report 2018 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Each year, the Gulf Research Program (GRP) produces an annual report to summarize how funds were used. These reports review accomplishments, highlight activities, and, over time, will assess metrics to determine how the program is progressing in accomplishing its goals. The 2018 annual report is the fifth report in this series. The GRP is an independent, science-based program founded in 2013. Through grants, fellowships, and other activities, it seeks to enhance oil system safety and the protection of human health and the environment in the Gulf of Mexico region and other areas along the U.S. outer continental shelf with offshore oil and gas operations. This report captures key developments and successes in 2018. The GRP continues to build on its past work and seeks to learn, think about, and plan for how and where it can have the greatest cumulative and lasting impacts.
Keywords: Environment and Environmental Studies

The Gulf Research Program Annual Report 2017 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Each year, the Gulf Research Program (GRP) produces an annual report to summarize how funds were used. These reports review accomplishments, highlight activities, and, over time, will assess metrics to determine how the program is progressing in accomplishing its goals. The 2017 annual report is the fourth report in this series.
Keywords: Environment and Environmental Studies

Navigating the Energy Transition in the Gulf of Mexico: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Today, with a changing climate putting pressure on communities and ecosystems worldwide, goals for a carbon-neutral economy mean that renewable and low-carbon energy sources are being presented as solutions. While these cleaner energy sources have the potential to reduce risk to the environment and bring energy security closer to a reality, questions remain about the stability of the energy supply chain, the ability to meet energy demand reliably, and the best ways to produce fair and equitable outcomes in an energy transition. To serve as a catalyst for developing new insights and coordination around the energy transition, the Gulf Research Program at the National Academies of Sciences, Engineering, and Medicine convened a 2-day workshop in Washington, DC, called Navigating the Energy Transition in the Gulf of Mexico. Based around two scenarios in the year 2050 - one in which a carbon neutral economy is achieved and another in which robust dependence on fossil fuels remains - this serious gaming event stimulated the sharing of ideas, concerns, and cascading impacts from participants across academia, industry, government, and Gulf communities. This publication summarizes the activities, presentations, and discussion of the workshop.
Keywords: Energy and Energy Conservation

Opportunities for the Gulf Research Program: Monitoring Ecosystem Restoration and Deep Water Environments: Summary of a Workshop - Waddell, Kim; Olson, Steve (The National Academies Press, 2015)
Environmental monitoring in the Gulf of Mexico poses extensive challenges and significant opportunities. Multiple jurisdictions manage this biogeographically and culturally diverse region, whose monitoring programs tend to be project-specific by design and funding. As a result, these programs form more of a monitoring patchwork then a network. At the same time, the Gulf monitoring community faces a unique opportunity to organize and think differently about monitoring - including how best to allocate and manage the resources for this large marine ecosystem and its communities - as a result of the infusion of resources for environmental restoration and related activities after the Deepwater Horizon oil spill. Opportunities for the Gulf Research Program: Monitoring Ecosystem Restoration and Deep Water Environments summarizes a Gulf Research Program workshop held on September 3-4, 2014 in New Orleans, Louisiana. The workshop gathered about 40 participants from the energy industry, state and federal government, academia, and nongovernmental organizations to examine two broad issues that were seen as time-sensitive opportunities in light of significant investments in the Gulf for restoration and accelerating development of energy resources in the deep Gulf: monitoring ecosystem restoration and deep water environments. As participants explored potential opportunities for the Program to consider, they noted the essential role that communication and outreach play in successful monitoring, and the importance of applying an ecosystem service approach to monitoring, forging partnerships among stakeholders, and supporting efforts to organize and manage monitoring data.
Keywords: Environment and Environmental Studies

The Gulf Research Program Annual Report 2016 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Each year, the Gulf Research Program (GRP) produces an annual report to summarize how funds were used. These reports review accomplishments, highlight activities, and, over time, will assess metrics to determine how the program is progressing in accomplishing its goals. The 2016 annual report is the third report in this series.
Keywords: Environment and Environmental Studies

Opportunities for the Gulf Research Program: Community Resilience and Health: Summary of a Workshop - Olsen, LeighAnne; Olson, Steve (The National Academies Press, 2015)
There are many connections between human communities and their surrounding environments that influence community resilience and health in the Gulf of Mexico. The impacts of the Deepwater Horizon oil spill on Gulf communities and ecosystems - coupled with the region's preexisting health challenges and environmental stressors - illustrate the need to better understand these connections. In the future, natural and man-made disasters, climate change impacts, and other environmental stressors will present complex challenges to the physical, mental, and social well-being of communities in the Gulf. Understanding the interrelationships among health, ecological, and economic impacts of disasters and other environmental stressors will be crucial to addressing these challenges. Opportunities for the Gulf Research Program: Community Resilience and Health summarizes a Gulf Research Program workshop held on September 22-23, 2014, in New Orleans, Louisiana. The workshop examined opportunities to improve the health, well-being, and resilience of communities in the Gulf region through discussions with about 50 participants with diverse expertise and experience. These discussions identified perceived needs, challenges, and opportunities that align with the Gulf Research Program's mission and goals - particularly its goal to improve understanding of the connections between human health and the environment to support the development of health and resilient Gulf communities. This workshop is expected to lead to the development of additional Program activities and opportunities for the research community.
Keywords: Conflict and Security Issues; Environment and Environmental Studies

An Approach for Assessing U.S. Gulf Coast Ecosystem Restoration: A Gulf Research Program Environmental Monitoring Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Valued for its ecological richness and economic value, the U.S. Gulf of Mexico is under substantial pressure from human activities. The Deepwater Horizon platform explosion and oil spill significantly damaged Gulf ecosystems and led to the largest ecological restoration investment in history. The unprecedented number and diversity of restoration activities provide valuable information for future restoration efforts, but assessment efforts are hampered by many factors, including the need to evaluate the interaction of multiple stressors and consider long-term environmental trends such as sea level rise, increasing hurricane intensity, and rising water temperatures. This report offers a comprehensive approach to assess restoration activities beyond the project scale in the face of a changing environment. A main component of this approach is using different types of scientific evidence to develop "multiple lines of evidence" to evaluate restoration efforts at regional scales and beyond, especially for projects that may be mutually reinforcing (synergistic) or in conflict (antagonistic). Because Gulf of Mexico ecosystems cross political boundaries, increased coordination and collaboration is needed, especially to develop standardized data collection, analysis, synthesis, and reporting. With these improvements, program-level adaptive management approaches can be used more effectively to assess restoration strategies against the backdrop of long-term environmental trends.
Keywords: Environment and Environmental Studies

The Gulf Research Program Annual Report 2015 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Each year, the Gulf Research Program produces an annual report to summarize how funds were used. These reports review accomplishments, highlight activities, and, over time, will assess metrics to determine how the program is progressing in accomplishing its goals. The 2015 annual report is the second report in this series.
Keywords: Environment and Environmental Studies

The Gulf Research Program: A Strategic Vision (The National Academies Press, 2014)
In 2010 the Deepwater Horizon explosion and fire in the Gulf of Mexico caused the largest offshore oil spill in U.S. history, resulting in significant impacts on the region's environment and residents. Legal settlements with the companies held responsible led the federal government to ask the National Academy of Sciences to form and administer a 30-year program to enhance oil system safety, human health, and environmental resources in the Gulf of Mexico and other U.S. continental shelf areas where offshore oil and gas exploration and production occur or are under consideration. The new Gulf Research Program will receive $500 million to support activities using three broad approaches: research and development, education and training, and environmental monitoring. The Gulf Research Program: A Strategic Vision establishes the Program's foundation and introduces its mission, goals, and objectives. It describes some initial activities and sets out the Program's vision for contributing lasting benefit to the Gulf region and the nation. The Program is an extraordinary opportunity to foster science on a regional scale and over the long term. The document will be of interest to scientists, health professionals, engineers, and educators who wish to learn about, collaborate with, and submit proposals to the Program, and to all those who share the goal of enhancing resilience in areas where offshore energy production, vibrant communities, and dynamic ecosystems coexist.
Keywords: Environment and Environmental Studies

Offshore Situation Room: Enhancing Resilience to Offshore Oil Disasters in the Gulf of Mexico: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
More than a decade after the Deepwater Horizon disaster, the Gulf Research Program convened a diverse group of 60 experts in a virtual event to inform its efforts to enhance resilience to future offshore oil disasters in the Gulf of Mexico region. The event, Offshore Situation Room, took place over three half-days during June 15-17, 2021, and had four main objectives: 1) develop a concise, prioritized list of questions that need to be addressed to support successful prevention, response, and recovery that would minimize the impacts of an offshore oil disaster; 2) provide a collaborative atmosphere where participants can share ideas, capabilities, and information, and build a community dedicated to the successful prevention of, response to, and recovery from an offshore oil spill disaster; 3) explore capabilities for and impediments to prevention, response, recovery, and understanding impacts of an offshore oil disaster in the Gulf of Mexico; and 4) highlight how changes in policy, response, resilience, and restoration efforts may affect outcomes of a major offshore incident. This publication summarizes the presentations and discussion of the event.
Keywords: Environment and Environmental Studies

Advancing Health and Resilience in the Gulf of Mexico Region: A Roadmap for Progress - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Consequences of natural disasters and the COVID-19 pandemic have taken a cumulative toll on the health and well-being of people in the Gulf of Mexico region. Long-standing societal challenges related to racism, poverty, education, housing, and underemployment are compounding the trauma, leading to chronic stress for many Gulf residents. The Committee on Progress Toward Human Health and Community Resilience in the Gulf of Mexico Region new report, Advancing Health and Community Resilience in the Gulf of Mexico Region: A Roadmap for Progress, explores key challenges and priorities in Gulf states, including Alabama, Florida, Louisiana, Mississippi, and Texas and evaluates recent progress. The report also makes recommendations for closing critical gaps and implementing transformative approaches that focus on the diverse needs and experiences of people who live and work in the Gulf region.
Keywords: Health and Medicine; Environment and Environmental Studies

Opportunities for the Gulf Research Program: Middle-Skilled Workforce Needs: Summary of a Workshop - National Research Council (The National Academies Press, 2014)
During the period 1990 to 2010, U.S. job growth occurred primarily in the high-skilled and low-skilled sectors. Yet, one-third of projected job growth for the period 2010-2020 will require middle-skilled workers -- who will earn strong middle-class wages and salaries -- important to both the production and consumption components of our economy. These jobs typically require significant training, often requiring more than a high school diploma but less than a baccalaureate degree. In the Gulf of Mexico, middle skilled workers play key roles in maintaining oil system safety, completing the numerous environmental restoration projects needed along the Gulf coast, and as workers in an integrated and resilient public health system. Educational pathways that lead to middle skilled jobs in these areas include: apprenticeship programs offered by schools, unions, and employers; high school career and technical education programs; community college courses, certificates, and associate degrees; and employer provided training. Opportunities for the Gulf Research Program: Middle-Skilled Workforce Needs is the summary of a workshop held on June 9-10, 2014 in Tampa, Florida. This workshop convened 40 thought leaders from the Gulf region's education, employer, and policymaking communities to facilitate a discussion of the current state of education and training pathways for preparing the region's middle-skilled workforce in both the short- and long-term and to identify perceived needs and potential opportunities that might be addressed by the GRP. Workshop participants discussed a variety of opportunities around building capacity in the region's middle-skilled workforce, including the need for competency-based education and training approaches and stronger partnerships among the region's employers and institutions of higher education.
Keywords: Industry and Labor

Investing in Resilient Infrastructure in the Gulf of Mexico: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
To help prioritize among possible investments to improve the resilience of built infrastructure in the Gulf of Mexico region, the National Academies of Sciences, Engineering, and Medicine convened a diverse group of experts for a 3-day interactive workshop on November 15, 16, and 18, 2021. This workshop was held as communities surrounding the Gulf continue to experience frequent, destructive disasters, some infrastructure in the region continues to degrade or fail from exceeded capacity and delayed maintenance and replacement, and climate change threatens previously unimagined impacts. The workshop, titled Investing in Resilient Infrastructure in the Gulf of Mexico, demonstrated and refined a process to help inform recommendations for prioritizing infrastructure investments across sectors and anchored in the Gulf region energy industry. This publication summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies